Analysis of Nginx Web Server Performance Using IPv6 with Load Balancing Method Based on Weighted Round Robin Algorithm Scheduling - Arifwidodo, Bongga (Journal of INISTA, 2025)
The need for the internet affects the growth in the number of website visitors and increases the server's traffic load. The increasing number of visitors often causes the website to overload due to an excessive number of requests despite the website still using a single server. So, it is necessary to apply Load Balancing techniques. The implementation requires an algorithm, specifically the Load Balancing method, which is responsible for dividing traffic as a workload among multiple servers. This research utilizes the Weighted Round Robin (WRR) algorithm, which considers server load based on device specifications. The scenario tests optimal performance load sharing among the WRR 1:1:1, WRR 2:1:1, and WRR 3:1:1 configurations then measures Response time and CPU Utilization. Testing is performed 30 times in each test scenario, and then the average value is taken. Giving traffic loads of 1000, 2000, and 3000 Requests using H2load Benchmark. The results of the WRR 2:1:1 ratio show that it is the most optimal, as the Load is evenly distributed among the three web servers. Reading the average CPU usage for 1000-3000 Request traffic, it reaches 71%-79% on Server 1, 47%-56% on Server 2, and 48%-56% on Server 3. Then, the average Response time is 223.77ms at 1000 Requests, 233.13ms at 2000 Requests, and 235.37ms at 3000 Requests.